2014
DOI: 10.15252/emmm.201302627
|View full text |Cite
|
Sign up to set email alerts
|

Emerging treatment strategies for glioblastoma multiforme

Abstract: Glioblastoma multiforme (GBM) is the deadliest form of brain tumor with a more than 90% 5-year mortality. GBM has a paltry median survival of 12.6 months attributed to the unique treatment limitations such as the high average age of onset, tumor location, and poor current understandings of the tumor pathophysiology. The resection techniques, chemotherapic strategies, and radiation therapy currently used to treat GBM have slowly evolved, but the improvements have not translated to marked increases in patient su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
307
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 312 publications
(312 citation statements)
references
References 90 publications
0
307
0
5
Order By: Relevance
“…Despite advances in surgical resection, radiotherapy, chemotherapy and other therapeutic approaches, including immune and gene therapy, the prognosis for patients with glioblastoma remains poor (3)(4)(5)(6)(7). A previous study demonstrated that the median survival time of patients with glioblastoma was 4.9 months following diagnosis (8).…”
Section: Introductionmentioning
confidence: 99%
“…Despite advances in surgical resection, radiotherapy, chemotherapy and other therapeutic approaches, including immune and gene therapy, the prognosis for patients with glioblastoma remains poor (3)(4)(5)(6)(7). A previous study demonstrated that the median survival time of patients with glioblastoma was 4.9 months following diagnosis (8).…”
Section: Introductionmentioning
confidence: 99%
“…All the above-cited mechanisms are becoming of utmost importance in understanding and treatment of the disease, (reviewed in Ref. 16). As all current therapeutic approaches provide poor success in prolonging patients' survival, a challenge is given for novel techniques, such glioblastoma-targeting by aptamers.…”
Section: Aptamers In Gliomamentioning
confidence: 99%
“…In brain tumours magnetic resonance imaging (MRI) represents a standard method for defining lesion boundaries (16) observed as spatially localized signal intensities, by which areas of relative darkness and brightness could be distinguished (31). For a more exact differentiation of GBM from the surrounding brain tissue, a positron emission tomography (PET) is used as a complementary technology (16). PET allows for acquiring images of the tumour boundaries by high-energy gamma-rays that are emitted from isotopelabeled natural biological molecules residing and being concentrated in the cancer cells (32), due to their altered metabolism.…”
Section: Clinical Applications Of Aptamers Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…It binds to VEGF-A ligand and therefore affects angiogenesis by inhibiting VEGF-endothelial cell interaction. Bevacizumab is active and approved for use in many tumor types [2].…”
Section: Introductionmentioning
confidence: 99%